Wood Modification in Europe A state-of-the-art about processes, products and applications - Jones, Dennis; Sandberg, Dick; Goli, Giacomo; Todaro, Luigi (Proceedings e report, 2019)
This report is a result of a questionnaire and subsequent collation of data, which outlines the current status of wood modification across Europe in terms of national inventories and groups that have reported current activity in the respective research areas covered in this report.